1979
DOI: 10.1097/00005072-197911000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Transverse Tubules in Induced Myotonia

Abstract: A single oral dose of clofibrate (30 mg/100 gm body weight) given to 250-300 gm male rats produced myotonic discharges from both the gastrocnemius and soleus muscles 2 hours after feeding. Rats fed the same dosage for 14 consecutive days exhibited electromyographic discharges consistent with profound myotonia. Fibers removed from the superficial region of the gastrocnemius muscle served as the source of fast twitch fibers for histological studies. Slow twitch fibers were observed in the soleus muscle. After a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1980
1980
1990
1990

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The transverse tubules, which are extensions of the surface membrane within the muscle fiber, have been implicated to play a key role in the genesis of electrical activity of the muscle (51) and have been shown to be affected in the muscle biopsies of patients with myotonia (52). Although we did not find any evidence of muscle damage with investigation by light microscopy (50), others have found extensive degeneration and necrosis of muscle fibers using a higher dose of clofibrate for a longer duration (53). Therefore, the alterations of protein and energy metabolism, together with the dilation of tranisverse tubules, are probably a subtle manifestation ofthe toxic effect of this drug on the skeletal muscle.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The transverse tubules, which are extensions of the surface membrane within the muscle fiber, have been implicated to play a key role in the genesis of electrical activity of the muscle (51) and have been shown to be affected in the muscle biopsies of patients with myotonia (52). Although we did not find any evidence of muscle damage with investigation by light microscopy (50), others have found extensive degeneration and necrosis of muscle fibers using a higher dose of clofibrate for a longer duration (53). Therefore, the alterations of protein and energy metabolism, together with the dilation of tranisverse tubules, are probably a subtle manifestation ofthe toxic effect of this drug on the skeletal muscle.…”
Section: Discussioncontrasting
confidence: 63%
“…Our previous electromyographic and electron microscopic studies revealed the development of myotonia and dilation of transverse tubules of skeletal muscle fibers of rats similarly treated wvith clofibrate (50). The transverse tubules, which are extensions of the surface membrane within the muscle fiber, have been implicated to play a key role in the genesis of electrical activity of the muscle (51) and have been shown to be affected in the muscle biopsies of patients with myotonia (52).…”
Section: Discussionmentioning
confidence: 98%